What does Life-Cycle Assessment of agricultural products need for more meaningful inclusion of biodiversity? - Teillard, Félix; de Souza, Danielle Maia; Thoma, Greg; Gerber, Pierre J.; Finn, John A. (The Journal of applied ecology, 2016)
1. Decision-makers increasingly use life-cycle assessment (LCA) as a tool to measure the environmental sustainability of products. LCA is of particular importance in globalized agricultural supply chains, which have environmental effects in multiple and spatially dispersed locations. 2. Incorporation of impacts on biodiversity that arise from agricultural production systems into environmental assessment methods is an emerging area of work in LCA, and current approaches have limitations, including the need for (i) improved assessment of impacts to biodiversity associated with agricultural production, (ii) inclusion of new biodiversity indicators (e.g. conservation value, functional diversity, ecosystem services) and (iii) inclusion of previously unaccounted modelling variables that go beyond land-use impacts (e.g. climate change, water and soil quality). 3. Synthesis and applications. Ecological models and understanding can contribute to address the limitations of current life-cycle assessment (LCA) methods in agricultural production systems and to make them more ecologically relevant. This will be necessary to ensure that biodiversity is not neglected in decision-making that relies on LCA.